Simultaneous wireless assessment of intra-oral pH and temperature. (August 2016) - Farella, M.; Loke, C.; Sander, S.; Songini, A.; Allen, M.; Mei, L.; Cannon, R.D.
Abstract: Objectives: Intra-oral pH plays an important role in the pathogenesis of tooth erosion and decay, but there is limited information about its variation in real life settings. The aims of this research were to: 1) develop a wireless device, which can be used to continuously monitor intra-oral pH and temperature in real-time; 2) test and validate the device under controlled laboratory conditions; and 3) collect data in a natural environment in a sample of healthy volunteers. Methods: A wireless device for measuring pH and temperature simultaneously was developed, calibrated and validated against the gold standard glass electrode pH meter. A smart phone was used as data logger. The wireless device was embedded in an oral appliance and worn by eleven participants (mean age 31.1 ± 6.9 years) for 24 h, while conducting standardised drinking tasks and regular daily activities. Results: The wireless device could accurately measure pH and temperature both in vitro and in vivo . The recovery time following the swallow of a standard acidic drink varied markedly among individuals (mean = 1.3 ± 0.9 min). The intra-oral pH and temperature recorded in the natural environment also showed a large inter- and intra-individual variability. The average intra-oral pH when asleep (6.7 ± 0.5) was lower (p < 0.001) than when awake (7.2 ± 0.5). The average intra-oral temperature during sleep (35.6 ± 0.5 °C) was higher (p < 0.001) than when awake (34.5 ± 0.7 °C). Conclusions: Intra-oral pH and temperature can be continuously and wirelessly assessed in real-life settings, and show individual-specific patterns with circadian variations. Intra-oral pH becomes slightly acidic during sleep while intra-oral temperature increases and fluctuates less. Clinical significance: We propose a wireless device that is capable of measuring intra-oral pH over a 24-h period. We found marked inter-individual variation after acidic stimuli, and day to sleep time variation of both intra-oral temperature and pH. Our approach may provide new insight into the relationship between oral pH, tooth wear and decay.